Sub-impacts of simply supported beam struck by steel sphere—part II: Numerical simulations - Xiaoli Qi; Xiaochun Yin (Advances in Mechanical Engineering, 2016)
This part of the article describes numerical simulations of the problem investigated experimentally. A three-dimensional finite element model of elastic–plastic for sphere falling on beam has been implemented using the nonlinear dynamic finite element software LS-DYNA. From the numerical simulations, it was found that the LS-DYNA is suitable to study complex sub-impact phenomenon, and good agreement is in general obtained between the simulation and experimental results. The numerical simulations show that the initial impact velocity, equivalent elasticity modulus, contact curvature radius of the sphere, and equivalent mass have great influence on the contact–impact time of the sub-impact, and an applicable range of the theoretical expression of contact–impact time of the sub-impact was determined. In addition, the numerical simulations demonstrate the ratios of maximum amplitudes of the first-, second-, and third-order vibrations to the maximum amplitudes of the beam vibrations, and the phase angle of the first-order vibration will change suddenly when the sub-impacts occur. Furthermore, the occurrence conditions of the sub-impacts were clarified numerically. It was found that the occurrence conditions of the sub-impacts can be represented by a mass ratio threshold, and the thickness or length of the beam has also a great influence on the occurrence of the sub-impacts. Once the sub-impacts occur, which would result in an uncertain behavior of the apparent coefficient of restitution.